2015
DOI: 10.5194/se-6-609-2015
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of degraded arable steppe soils in Moldova using vetch as green manure

Abstract: Abstract. In the Republic of Moldova, non-sustainable arable farming led to severe degradation and erosion of fertile steppe soils (Chernozems). As a result, the Chernozems lost about 40 % of their initial amounts of soil organic carbon (SOC). The aim of this study was to remediate degraded arable soils and promote carbon sequestration by implementation of cover cropping and green manuring in Moldova. Thereby, the suitability of the legume hairy vetch (Vicia sativa) as cover crop under the dry continental clim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 63 publications
(69 reference statements)
2
18
0
1
Order By: Relevance
“…At the two experimental sites in Orhei and Cahul, hairy vetch was used as cover crop, which is a high yielding species that may be also suitable under dry conditions and additionally fixes large amounts of atmospheric nitrogen (Teasdale, Devine, Mosjidis, Bellinder, & Beste, ; Tenopala, Gonzalez, & de la Barrera, ). Our study indicated that cover cropping using hairy vetch is an effective C sequestration option with a total rate of 0.8 t ha −1 yr −1 in the 0‐ to 10‐cm layer and 1.0 t ha −1 yr −1 in the 10‐ to 30‐cm layer, although these values are lower than very high rates directly after implementation (Wiesmeier, Lungu, et al, ). The measured C sequestration rate is substantially higher than global mean estimates for cover crops (Poeplau & Don, ), but within the range of other studies that specifically investigated sites under hairy vetch (0.2 to 2.7; see Wiesmeier, Lungu, et al, , and references therein).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…At the two experimental sites in Orhei and Cahul, hairy vetch was used as cover crop, which is a high yielding species that may be also suitable under dry conditions and additionally fixes large amounts of atmospheric nitrogen (Teasdale, Devine, Mosjidis, Bellinder, & Beste, ; Tenopala, Gonzalez, & de la Barrera, ). Our study indicated that cover cropping using hairy vetch is an effective C sequestration option with a total rate of 0.8 t ha −1 yr −1 in the 0‐ to 10‐cm layer and 1.0 t ha −1 yr −1 in the 10‐ to 30‐cm layer, although these values are lower than very high rates directly after implementation (Wiesmeier, Lungu, et al, ). The measured C sequestration rate is substantially higher than global mean estimates for cover crops (Poeplau & Don, ), but within the range of other studies that specifically investigated sites under hairy vetch (0.2 to 2.7; see Wiesmeier, Lungu, et al, , and references therein).…”
Section: Discussionmentioning
confidence: 69%
“…Our study indicated that cover cropping using hairy vetch is an effective C sequestration option with a total rate of 0.8 t ha −1 yr −1 in the 0‐ to 10‐cm layer and 1.0 t ha −1 yr −1 in the 10‐ to 30‐cm layer, although these values are lower than very high rates directly after implementation (Wiesmeier, Lungu, et al, ). The measured C sequestration rate is substantially higher than global mean estimates for cover crops (Poeplau & Don, ), but within the range of other studies that specifically investigated sites under hairy vetch (0.2 to 2.7; see Wiesmeier, Lungu, et al, , and references therein). The fine fraction‐based OC sequestration rate in the 0‐ to 10‐cm layer is only slightly lower than the total rate as a high proportion of OC was found in the fine fraction.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…XTB-5 is an attractive microorganism for environment remediation and agronomic applications. Moreover, microbial remediation, especially combined phytoremediation, is important to reduce land degradation (Glenn et al, 2016;Wiesmeier et al, 2015).…”
Section: Discussionmentioning
confidence: 99%